Analysis of The Effectiveness of Covid-19 Prevention Measures in Manado City Using the K-means Method - Wikarsa, Liza; Pandelaki, Steven; Kurnia, Henrico (Jurnal Pekommas, 2022)
Covid-19 is an infectious disease caused by the Coronavirus, spreading quickly and resulting in death. Thus, the government of Manado city recommends all the residents always comply with the   Covid-19 health protocols. The study aimed to investigate the public's response to the effectiveness of the Covid-19 prevention measures imposed by the local government. The prevention measures include using masks, healthy lifestyles, clean lifestyles, and social distancing. K-means clustering was used to determine the level of effectiveness of prevention measures into four clusters, namely very effective (C1), moderately effective (C2), ineffective (C3), and very ineffective (C4). This algorithm yields consistent results despite the difficulty of predicting the K-values or the number of clusters at the beginning of the algorithm. As a result, 58% of respondents consider the prevention measures very effective. They have a high level of Covid-19 awareness and the consequences of violating the health protocols, even though about 10% of the respondents doubted the health protocols in Manado were effective due to the high number of death cases daily. The results can be used as insights for the local government to stop the spread of the Coronavirus in Manado city.